Gestational Trophoblastic Disease Electronic Consults: What Do Patients and Physicians Want to Know?. Issue 4 (1st May 2018) - Nitecki, Roni; Berkowitz, Ross S.; Elias, Kevin M.; Goldstein, Donald P.; Horowitz, Neil S.
Abstract : Objectives: Given the rarity of gestational trophoblastic disease (GTD), specialized regional and national centers for GTD have been established. These centers serve at least 3 purposes: to improve care for women with GTD, to enhance research though collaboration, and to educate other clinicians. This study was undertaken to understand the potential GTD knowledge gap by examining both patient and physician inquiries received at a specialized GTD center. Methods: All electronic consults received by specialists at our center between March 2016 and March 2017 were analyzed. Information collected included source of inquiry, reason for the consult, type of GTD, and the advice provided. Descriptive statistics were used to analyze the major trends. Results: We analyzed 102 electronic consults. Physicians sent 49 (48%) and patients sent 53 (52%) consults. Most e-consults were sent by physicians and patients within the United States; however, 11% of the consults were directed from international locations. Among physicians, gynecologic oncologists (65%) were the most common specialty to consult our institution followed by medical oncologists (18%) and obstetrician gynecologists (16%). Most questions from gynecologic (62%) and medical oncologists (77%) concerned treatment regimens. This was contrasted by general obstetrician gynecologists who more commonly asked about human chorionic gonadotropin monitoring (62%). Difficulty with appropriate Federation of Gynecology and Obstetrics staging and World Health Organization risk score assignment were common themes. Most of the confusion centered on the use of chest computed tomography rather than plain chest x-ray for the assessment of lung metastases. Unlike physicians, patient e-consults were most concerned with the duration of human chorionic gonadotropin monitoring (51%) and timing of future conceptions. Conclusions: Both physicians and patients in the United States and abroad frequently use electronic consults to improve their knowledge about GTD management and follow-up. Although the type of inquires varied, they highlight fundamental gaps in understanding and potential opportunities for formal education.